2015
DOI: 10.1111/mec.13174
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis reveals a positive correlation between genetic diversity metrics and environmental status in the long‐lived seagrassPosidonia oceanica

Abstract: The seagrass Posidonia oceanica is a key engineering species structuring coastal marine systems throughout much of the Mediterranean basin. Its decline is of concern, leading to the search for short- and long-term indicators of seagrass health. Using ArcGIS maps from a recent, high-resolution (1-4 km) modelling study of 18 disturbance factors affecting coastal marine systems across the Mediterranean (Micheli et al. 2013, http://globalmarine.nceas.ucsb.edu/mediterranean/), we tested for correlations with geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 71 publications
1
43
0
Order By: Relevance
“…However, recent studies indicated that temperature variation rather than mean value could be the main trigger of flowering (Diaz-Almela et al, 2007). Since the genetic diversity of some meadows in the biogeographic transition zone appears be higher compared to others meadows of the Mediterranean (Jahnke et al, 2015), future studies should investigate whether there is a relationship between the success of seed production in these meadows and their genetic diversity. Flowering had rarely been observed before 1984 along the coasts of Corsica and Livorno (Caye and Meinesz, 1984), but from 1994 onward this phenomenon occurred regularly (Balestri, 2004; Gobert et al, 2005), possibly due to moderate warming of the northwestern Mediterranean over the past decades (Lejeusne et al, 2010; Marbà et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies indicated that temperature variation rather than mean value could be the main trigger of flowering (Diaz-Almela et al, 2007). Since the genetic diversity of some meadows in the biogeographic transition zone appears be higher compared to others meadows of the Mediterranean (Jahnke et al, 2015), future studies should investigate whether there is a relationship between the success of seed production in these meadows and their genetic diversity. Flowering had rarely been observed before 1984 along the coasts of Corsica and Livorno (Caye and Meinesz, 1984), but from 1994 onward this phenomenon occurred regularly (Balestri, 2004; Gobert et al, 2005), possibly due to moderate warming of the northwestern Mediterranean over the past decades (Lejeusne et al, 2010; Marbà et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, whereas the genetic make‐up is a permanent characteristic of a plant, and patch genetic structure may require years to decades to change (see for instance Zupo et al . ; Jahnke, Olsen & Procaccini ), nutrient levels and the amount of herbivory may have changed between the time of flower induction and when ecological data were collected.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, if those cues do not exist locally, populations in a given area may only subsist via asexual reproduction, with important implications for their future (Honnay & Jacquemyn ; Hughes & Stachowicz ; Oliva et al . ; Jahnke, Olsen & Procaccini ).…”
Section: Introductionmentioning
confidence: 99%
“…In seagrasses this is a critical life stage since, in some species, sexual reproduction is very variable in space and time and in general, there is a very low rate of seedling establishment12. Although some seagrass species rely mainly on clonal reproduction, sexual reproduction provides genetic diversity which could make seagrass populations more resilient and resistant to future changes13. Furthermore, seeds and seedlings provide a key opportunity to colonize new habitats14, and under the current scenarios of anthropogenic threats, this strategy may be particularly relevant for allowing the establishment of seagrass into more suitable environments.…”
mentioning
confidence: 99%